Analisis Efektivitas Sistem Informasi Akuntansi Hotel Berbintang Di Kota Surakarta - Andriani Putri Wihartati; Yuwita Ariessa Pravasanti; Maya Widyana Dewi (Nur Science Institute, 2023)
This study aims to analyze the effect of accounting manager knowledge, management participation and information technology sophistication on the effectiveness of accounting information systems in hotels in Surakarta City as the research population. Sampling in this study used a simple random sampling technique and the sample size was determined by the slovin formula. The data used is primary data in the form of a questionnaire. The data analysis method used in this study is multiple linear regression analysis with a significance level of 5% or 0.05. The results of this study indicate that management participation and the sophistication of information technology have a significant effect on the effectiveness of accounting information systems. Meanwhile, knowledge of accounting managers has no significant effect on the effectiveness of accounting information systems. Keywords: Knowledge of accounting managers, management participation, sophistication of information technology, effectiveness of accounting information systems.